A nonpharmacological approach to improve sleep quality in older adults. (10th October 2017) - Rawtaer, Iris; Mahendran, Rathi; Chan, Hui Yu; Lei, Feng; Kua, Ee Heok
Abstract : Objectives: Poor sleep quality is highly prevalent among older adults and is associated with poor quality of life, cognitive and physical decline, depression, and increased mortality. Medication options commonly used are not ideal, and alternative treatment strategies are needed. We evaluate a community‐based psychosocial intervention program and its effect on sleep quality in older adults. Method: Elderly participants aged 60 and above were included. Those with Geriatric Depression Scale and Geriatric Anxiety Inventory scores above 5 and 10, respectively, were excluded. The community program included tai chi exercise, art therapy, mindfulness awareness practice, and music reminiscence therapy. Pittsburgh Sleep Quality Index, Geriatric Depression Scale, and Geriatric Anxiety Inventory were administered at baseline and at 1 year. Results: A hundred and eighty‐nine subjects (44 men, 145 women; mean age = 69 years, SD = 5.7, range = 60‐89) participated. The proportion of participants with good sleep quality had increased from 58.2% to 64.6%. Sleep disturbance was significantly reduced (baseline, 1.04; postintervention, 0.76; mean difference 0.28; P  < .01); men experienced greater improvement ( P  < .001). Improvements were independent of changes in depressive and anxiety symptoms. Conclusion: Participation in this community program led to positive effects on sleep disturbances after a year. Psychosocial interventions have potential as a nondrug intervention approach for sleep problems, and further research is needed to understand its mediating mechanisms